DHVANI AND DANCE- CAN THERE BE A RELATIONSHIP? - Krishna, Pujita (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Dhvani or the idea of suggestion being the main cause for the experience of ‘rasa’ as expostulated in Anandavardhana’s seminal work Dhvanyaloka, became a game-changing idea in the field of poetics or aesthetics in its time. Not only was it comprehensive in its scope, but it also reinforced the pre-eminence of rasa in poetic works. The purpose of this article is merely exploratory in attempting to investigate if the concept of ‘dhvani’ as an aesthetic lens can be applied to dance as a performing art that is as communicative in its scope and intent as poetry. The article has been written from the perspective of being a practitioner of dance and as one who has written on dance as well. Since this is unexplored ground, I am only hoping to skim the surface of what I think can be a potential area for more in-depth research.